If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3)(7 + -1x) = 0 Reorder the terms: (-3 + 2x)(7 + -1x) = 0 Multiply (-3 + 2x) * (7 + -1x) (-3(7 + -1x) + 2x * (7 + -1x)) = 0 ((7 * -3 + -1x * -3) + 2x * (7 + -1x)) = 0 ((-21 + 3x) + 2x * (7 + -1x)) = 0 (-21 + 3x + (7 * 2x + -1x * 2x)) = 0 (-21 + 3x + (14x + -2x2)) = 0 Combine like terms: 3x + 14x = 17x (-21 + 17x + -2x2) = 0 Solving -21 + 17x + -2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-7 + x)(3 + -2x) = 0Subproblem 1
Set the factor '(-7 + x)' equal to zero and attempt to solve: Simplifying -7 + x = 0 Solving -7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + x = 0 + 7 x = 0 + 7 Combine like terms: 0 + 7 = 7 x = 7 Simplifying x = 7Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {7, 1.5}
| f/7=12 | | 8+-32u= | | 0.5(x-10)=9+4x | | (1/16)^(-3/2) | | 8-(4-7)= | | 27+3x=4(-x+3)-27 | | 10+r=3r+18 | | 5(2a-4)=(2a+4) | | =c/ | | 36x(36x)=173 | | 16+3.50h=11+4.75h | | -4(x+1)=24 | | 8k^2=-48k | | 1.5x-2=x+17 | | 2y+6-4y=-10 | | n+93=-277 | | 4(3y+6)=6(2y+4) | | 3/5g-4=9 | | 18y-18=-72 | | 7/2=4x | | 2.5d+7.75=1+3.25d | | 64/(2x4) | | 7x+5-2x-3=5x+4-x+2 | | u=0x+1 | | -7z-8+3z=3 | | 245y(245y)-180=0 | | 2(9+3)=4n-2 | | 0.75s-1.75=0.625+0.75 | | 3x/4-2=a | | 8=6-2y | | -6y-11=2y+21 | | x+8+x=22 |